Naturalistic audio-movies reveal common spatial organization across "visual" cortices of different blind individuals - Musz, Elizabeth; Loiotile, Rita E; Chen, Janice; Bedny, Marina (bioRxiv, 2021)
Occipital cortices of different sighted people contain analogous maps of visual information (e.g., foveal vs. peripheral space). In congenital blindness, "visual" cortices enhance responses to nonvisual stimuli. Do deafferented visual cortices of different blind people represent common informational maps? We leverage a naturalistic stimulus paradigm and inter-subject pattern similarity analysis to address this question. Blindfolded sighted (S, n=22) and congenitally blind (CB, n=22) participants listened to three auditory excerpts from movies; a naturalistic spoken narrative; and matched degraded auditory stimuli (i.e., shuffled sentences and backwards speech) while undergoing fMRI scanning. In a parcel-based whole brain analysis, we measured the spatial activity patterns evoked by each unique, ten-second segment of each auditory clip. We then compared each subject's spatial pattern to that of all other subjects in the same group (CB or S) within and across segments. In both blind and sighted groups, segments of meaningful auditory stimuli produced distinctive patterns of activity that were shared across individuals. Crucially, only in the CB group, this segment-specific, cross-subject pattern similarity effect emerged in visual cortex, but only for meaningful naturalistic stimuli and not backwards speech. These results suggest that spatial activity patterns within deafferented visual cortices encode meaningful, segment-level information contained in naturalistic auditory stimuli, and that these representations are spatially organized in a similar fashion across blind individuals. Competing Interest Statement The authors have declared no competing interest.